Pengolahan Limbah Kulit Singkong Menjadi Pupuk Organik Cair (POC) sebagai Upaya Pemberdayaan Masyarakat dan Pertanian Berkelanjutan di Desa Candibinangun Kecamatan Sukorejo Kabupaten Pasuruan - Rossa Ilma Silfiah; Muh Aniar Hari Swasono; Muhammad Ridwan Alviansyah; Kholidiyah Masruroh; Siti Musfita Sari; Denbagas Artamara (El-Mujtama: Jurnal Pengabdian Masyarakat, 2026)
Candibinangun Village, located in Sukorejo District, is an area active in cassava farming and processing, which provides a source of income for the local population. This activity generates significant amounts of waste in the form of cassava peels, but its utilization is not optimal, often leading to accumulation of organic waste and negative environmental impacts. This community service program aims to improve the community's knowledge and skills in processing cassava peel waste into liquid organic fertilizer (POC), an environmentally friendly and economically valuable alternative fertilizer. The method used in this community service is a participatory approach that includes field observation, outreach, training in POC production, fermentation assistance, and evaluation of the activity results. This liquid organic fertilizer is made through a fermentation process using cassava peels, EM4, molasses, and water for approximately 14 days. The results of this program indicate that the community is able to understand how to process cassava peel waste into POC and has begun applying the fertilizer to their agricultural land. In addition to helping reduce environmental pollution from organic waste, this activity also contributes to raising public awareness of the importance of sustainable agriculture and opens up opportunities for developing organic fertilizer-based businesses. Utilizing cassava peel waste to produce liquid organic fertilizer (POC) could be a solution for creating a circular economy at the village level and simultaneously reducing farmers' dependence on chemical fertilizers.